MENINGKATKAN HASIL TANAMAN STROBERI DENGAN URINE KELINCI - Yulia Eko Susilowati1; Rahayu Sarwitri (Universitas Tidar, 2018)
The research was to study of rabbit urine dose and interval given on the yield of strawberry plant. This research was conducted at Sumber village district of Dukun regency of Magelang and Kalikuto village district of Grabag regency of Magelang, since June to October 2016. Two treatment factors were arranged in Randomized Complete Block Design with tree replications. The first factor was rabbit urine dose of four levels i.e. 150, 300, 450, 600 ml/plant. The two factor was interval given of tree leves i.e. every 5, 10, 15 days. The result of this research in district of Dukun and district of Grabag showed that rabit urine dose 300 ml/plant give hight yield on number of bunches of flower, number of flower, number of fruit, weight of fruit, weight per fruit per plant. Interval given of rabit urine 10 days give hight yield on number of fruit and weight of fruit per plant. Urine dose of rabbit and interval given on the yield of is not interaction on all observation parameters